Prospective Teachers' Perspectives On Differentiated Instruction in Mathematics (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2025)
The pursuit of inclusive mathematics instruction requires educators to adopt adaptive teaching approaches, with differentiated instruction (DI) emerging as a key component. This study explores how future mathematics teachers perceive DI, especially regarding their grasp of its core principles, confidence in instructional application, preparedness to implement, and perspectives on its advantages and obstacles. Employing a descriptive quantitative access, data were collected through a 50-item Likert-scale questionnaire administered to 25 mathematics education students from three universities in Indonesia. The findings affirm comprehensive favorable attitudes toward DI, with mean scores ranging between 3.98 and 4.01. Respondents advertised strong theoretical comprehension of DI and showed enthusiasm about integrating it into their teaching practices. However, challenges such as limited instructional time and deficient firsthand experience in crafting differentiated lessons were acknowledged. These acumen highlight the importance of assimilation more practical, experience-based training within teacher education programs to equip future educators for implementing inclusive and differentiated teaching effectively.